Pengaruh Biaya Kualitas terhadap Produktivitas: (Studi Kasus pada Mouza Indonesia) - Hafsari, Novia Dwi; Hastuti, Hastuti (Indonesian Accounting Literacy Journal, 2025)
Abstract: Mouza Indonesia is a fashion company based in Kav. Pindad Bandung City was established in 2016. This study focuses on the impact of quality costs to determine whether there is a relationship between prevention costs, evaluation costs, internal failure costs and external failure costs on production productivity. The methods used in this study are descriptive statistics and classical acceptance tests consisting of normality tests and multiple regression analysis. The expected result of this study is to reduce the occurrence of defective products in the production process and increase production productivity by taking into account the cost of quality. As a result of this study, partial hypothesis testing was conducted on prevention costs, evaluation costs, internal failure costs and external failure costs, some of which had no significant impact on productivity. Then simultaneously conduct hypothesis testing on total costs that have a significant impact on productivity. Keywords: quality costs, productivity, defect products, Mouza Indonesia, production